Prevalence of growth hormone deficiency in brain tumor survivors: a systematic review and meta-analysis - Tatiana Tselovalnikova; Ben Ponvilawan; Maria G Pavlova; Cynthia Flanagan; Sunpreet S Rakhra; Betty M Drees (Endocrine Oncology)
Objective: To evaluate the prevalence of growth hormone deficiency in patients who underwent cranial irradiation for brain tumors. Methods: Ovid Medline and Embase databases were used for review. Eligible studies were observational studies with brain tumor survivors who had growth hormone function evaluated after treatment at age ≥18 years. Patient data on disease prevalence were pooled using the random-effect, generic inverse variance method. The presence of publication bias was determined by Egger’s test. Mann–Whitney U test, univariate and multivariate linear regression were used to determine the association and effect of covariates and growth hormone peak level. Results: After screening 3,355 relevant articles, seven studies were included. The pooled result showed that out of 3,489 patients who received radiation for brain tumors, regardless of age at the time of treatment, 50% developed growth hormone deficiency (95% CI 40–60%, I2 = 83%). Subgroup analysis based on the growth hormone peak level did not show differences between different cutoffs. Univariate linear regression using data from 27 patients showed that age at radiation and the time duration between radiation and the stimulation test (P = 0.03 and 0.002, respectively), but not radiation dose or sex, were significantly correlated with growth hormone peak level. After multivariate adjustment, only the time duration between radiation and the stimulation test was associated with decreased growth hormone peak level (P = 0.04). Conclusions: Half of brain tumor survivors develop growth hormone deficiency. A longer duration of follow-up is associated with higher risks of growth hormone deficiency. Lifelong follow-up is essential.